Estrategias para una matemática más cercana en tiempos de distanciamiento - Vargas Ramírez, Grace (2020)
The purpose of this document is to show the reality of a rural educational community with little or no connectivity and the way in which distance learning of mathematics was approached with a second grade group with students aged between 7 and 8 years, using various strategies in accordance with: the official Mathematics programs of the Ministry of Public Education of Costa Rica, the reality of the families and the resources available in their homes. In designing the activities, the skills integration material available from the Ministry body was used. It is highlighted that with the activities included in the Autonomous Work Guidelines, it was possible to give continuity to the education process using solving contextualized problems as the main methodological strategy.